Antioxidative and neuroprotective effects of volatile components in essential oils from Chrysanthemum indicum Linné flowers - Lee, Bong Han; Nam, Tea Gyu; Park, Woo Jung; Kang, Hee; Heo, Ho Jin; Chung, Dae Kyun; Kim, Gun Hee; Kim, Dae-Ok (Food science and biotechnology, 2015)
Chrysanthemum indicum Linné, belonging to the family Compositae, is a perennial herb that is widespread in Korea. C. indicum Linné flowers have been traditionally used as an oriental medicine for treatment of infectious diseases. The chemical compositions, antioxidant capacity, and neuroprotective effects of volatile components in essential oils from C. indicum Linné flowers were investigated. GC-MS analysis of essential oils revealed the 15 major components of 1,8-cineole, o -cymene, camphor, pinocarvone, chrysanthenyl acetate, bornyl acetate, trans -caryophyllene, terpinen-4-ol, umbellulone, trans -pinocarveol, cis -verbenol, borneol, α-terpineol, caryophyllene oxide, and thymol. Thymol had the highest antioxidant capacity. Essential oils and thymol dose-dependently decreased intracellular oxidative stress, exhibited anticholinesterase activities, and increased the cell viability of neuronal PC-12 cells. Essential oils and thymol from C. indicum Linné flowers can be sources of natural antioxidants and functional foods.